Dermal duct tumor with prominent ductal and sebaceous differentiation - Yong Huang (Wolters Kluwer Medknow Publications, 2013)
Dermal duct tumor is a rare, benign tumor. Clinically, dermal duct tumor presents as a firm papule, plaque or nodule, particularly on the lower limbs or head and neck region. Dermal duct tumor is been classified as poroma. Poroma can have divergent differentiation, but showing prominent ductal and sebaceous differentiation is rare. We present a case of dermal duct tumor with prominent ductal and sebaceous differentiation arising in the scalp. A 45-year-old man with a painless slow-growing, elevated, brownish nodule on his scalp of 7-year duration was admitted to our hospital. Histopathology revealed dermal duct tumor. The neoplasm also showed prominent ductal and sebaceous differentiation.